2021
DOI: 10.47738/ijiis.v4i1.76
|View full text |Cite
|
Sign up to set email alerts
|

implementing the Expected Goal (xG) model to predict scores in soccer matches

Abstract: Football is a sport that has the most fans in the world. What makes sebak patterns so popular are their uncertain and unpredictable results. There are many factors that affect the outcome of a football match, including strategy, skill, and even luck. Therefore, guessing the results of a soccer match is an interesting problem. All shots are grouped into sections on the playing field and theoretical goal scores are applied to each area. The factors analyzed are: distance of shot from goal and angle of shot in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…They use tree-based classification: XGBoost, Random Forest, Light GBM and CatBoost, also propose utilising Aggregated Profiles (AP) to demonstrate the difference in model predictions depending on a change in the value of a feature. (Umami et al, 2021) use factors such as distance and angle of shot on goal. Utilising Distance and Angle as one combined variable, this paper demonstrates that it had a greater impact on calculating the xG.…”
Section: Academic Look To the Xg Metricmentioning
confidence: 99%
“…They use tree-based classification: XGBoost, Random Forest, Light GBM and CatBoost, also propose utilising Aggregated Profiles (AP) to demonstrate the difference in model predictions depending on a change in the value of a feature. (Umami et al, 2021) use factors such as distance and angle of shot on goal. Utilising Distance and Angle as one combined variable, this paper demonstrates that it had a greater impact on calculating the xG.…”
Section: Academic Look To the Xg Metricmentioning
confidence: 99%
“…Given the game's low-scoring nature, understanding and pre-processing the dataset is crucial in model training. Eggels et al [18], Anzer and Bauer [19], Haaren [14] and Umami [15] take the raw positional x and y data to train the model. Mustafa Cavus and Przemyslaw Biecek [20] utilise simple trigonometry to convert these position values to angle and distance values to the centre of the opposition's goal.…”
Section: Processing Datamentioning
confidence: 99%
“…We compared the performance of our proposed models with the models presented in the literature of Eggels et al [18], Anzer and Bauer [19], Haaren [14], Umami [15], Cavus and Biecek [20], in terms of precision, recall, accuracy, F1, AUC and Brier Loss in Table 3. The comparison uses these measures since the respective authors of these papers reported the performance of the models along the same.…”
Section: Models Comparisonmentioning
confidence: 99%
“…It is not clear when the expected goals statistic was first developed and who conceived it, with most [ 1 , 9 , 10 ] stating that Macdonald’s [ 11 ] study into shot outcome in ice hockey originated the term, whilst others [ 3 ] have attributed it to Green’s [ 12 ] article. At its core, the concept of expected goals can be thought of as a classification problem (due to it being a probability of a shot being on target) this is why, in order to calculate these probabilities, machine learning and statistical methods are applied.…”
Section: Introductionmentioning
confidence: 99%